Tinjauan Filosofis Terhadap Undang-undang Nomor 23 Tahun 2011 Tentang Pengelolaan Zakat - Nor Mohammad Abdoeh (Cakrawala: Jurnal Studi Islam, 2019)
Zakat is an Islamic teaching that aims to realize the welfare of society. Islam wants and hopes for an equitable distribution of income, so wealth does not only revolve around a particular group. Indonesia as the largest Muslim majority country in the world has serious attention to the management of zakat funds. This is evidenced by the enactment of Regulation No. 23 of 2011 on the management of zakat. The purpose of this paper is to determine the nature and substance of the regulation. This research with a philosophical approach that is by explaining the nature and wisdom of the formal object. The result shows that the essence of this rule is none other than to accommodate the Muzakki and Mustahiq for the welfare of society